2013
DOI: 10.1111/geb.12054
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of regional establishment success and spread of introduced non‐indigenous vertebrates

Abstract: AimTo provide the first analysis of predictors of both establishment and spread, both within and across taxa, for all vertebrate taxa within a region. We used Florida, USA, as our study system because it has a well-documented history of introduction and invasion, and is a hotspot for biological invasions.Location Florida, USA. MethodsWe analysed non-indigenous species (NIS) data from peninsular Florida -which included both successful and unsuccessful introductions from all vertebrate classes -to determine the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
44
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 56 publications
(83 reference statements)
4
44
1
Order By: Relevance
“…The native range of C. hildmannianus is, however, about forty times that of E. grusonii. Several studies have argued that species with large native ranges possess a suite of traits that contribute to fitness and dispersal (Booth et al 2003), and have wide environmental tolerances which improves their ability to handle different conditions in new areas (Allen et al 2013, Lavoie et al 2013. We believe that this is especially true for the family Cactaceae, one of the families with the highest number of endangered species in the plant kingdom (Hernandez andBarcenas 1996, Goettsch et al 2015).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The native range of C. hildmannianus is, however, about forty times that of E. grusonii. Several studies have argued that species with large native ranges possess a suite of traits that contribute to fitness and dispersal (Booth et al 2003), and have wide environmental tolerances which improves their ability to handle different conditions in new areas (Allen et al 2013, Lavoie et al 2013. We believe that this is especially true for the family Cactaceae, one of the families with the highest number of endangered species in the plant kingdom (Hernandez andBarcenas 1996, Goettsch et al 2015).…”
Section: Discussionmentioning
confidence: 91%
“…Many studies have shown positive relationship between native range size and invasiveness (e.g. Duncan et al 2001, Forsyth et al 2004, Shah et al 2012, Allen et al 2013, Bates et al 2013. One potential explanation is that widespread species are more likely to be encountered and introduced to other regions (Pyšek and Richardson 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Within each iteration of the adaptive iSDM framework, the invasive species of interest, its stage within the invasion process [e.g., transport, establishment, spread or impact (Williamson 1996;Lockwood et al 2007)], and the ecosystem being invaded should be clearly specified, because the facilitators and inhibitors of biological invasions differ among taxa, invasion stages, and geographic locations (Hobbs and Humphries 1995;Theoharides and Dukes 2007;Allen et al 2013). It follows then, that these specifications may subsequently influence predictor variable selection (i.e., step 5), as well as the utility of model predictions for informing management (i.e., step 9).…”
Section: Introductionmentioning
confidence: 99%
“…It follows then, that these specifications may subsequently influence predictor variable selection (i.e., step 5), as well as the utility of model predictions for informing management (i.e., step 9). For instance, factors promoting species transport from native to novel ranges (e.g., human travel and trade) may be entirely different than those facilitating their spread in new environments (e.g., competitor absence) (Lockwood et al 2007;Allen et al 2013;Bradley et al 2015). Alternatively, a single factor, such as landscape structure (i.e., spatial patterns in habitat and resource patch arrangement) might affect a species differently at each invasion stage (Higgins et al 1996;.…”
Section: Introductionmentioning
confidence: 99%
“…This traditional view of invasions and associated approaches to management have become increasingly contested as economically inefficient, ecologically (and evolutionarily) ineffective and potentially undesirable in many cases (Angeler et al, 2012;Allen et al, 2013;Lotz and Allen, 2013). Some invasions may have neutral or positive outcomes (both real and perceived) (e.g., Sax et al, 2002), because they either reinforce specific ecosystem functions or provide economic benefit (e.g., Thomsen, 2010;Wallach et al, 2015;Weigel et al, 2016).…”
Section: Introductionmentioning
confidence: 99%